Efektivitas Bantuan Langsung Tunai Dana Desa pada Masyarakat Desa Tonuwotan Kecamatan Adonara Barat Kabupaten Flores Timur - Agustinus Beda Werang; Nikson Tameno; Novi Theresia Kiak (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to determine the effectiveness of the direct village fund cash assistance program for the community in Tonuwotan Village, West Adonara District, East Flores Regency. The type of research used in this research is field research. The research approach used in this research is a qualitative approach. The type of data used in this research is qualitative and quantitative data, while the data sources are primary and secondary data, as well as data collection techniques through observation, interviews and documentation. The informants in this research were 30 people, including 5 people from Tonuwotan government and 25 community recipients of the program. The results of the research show that the effectiveness of the Village Fund Direct Cash Assistance Program for the Community in Tonuwotan Village, West Adonara District, East Flores Regency has been effective, characterized by understanding the program, right on target, on time, achieving goals, real change, where the benefits have been felt by the community, namely that there is a positive impact from the benefits of Village Fund BLT which can help the community meet their daily needs or basic needs.